Mencius on Management:: Managerial Implications of the Writings of China’s Second Sage - Rarick, Charles (Journal of Comparative International Management, 2008)
Often referred to as China’s Second Sage, Mencius maintained and strengthened the Confucian tradition and added his own views on topics that are relevant to modern day managers. Mencius made managerial recommendations in such diverse areas as corporate governance, interpersonal relations, economic development, and human resources. The focus of this paper will be on Mencius’ management and leadership advice.